2016
DOI: 10.1088/1361-665x/26/1/015008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of introducing nonlinear components for a random excited hybrid energy harvester

Abstract: This work is mainly devoted to discussing the effects of introducing nonlinear components for a hybrid energy harvester under random excitation. For two different types of nonlinear hybrid energy harvesters subjected to random excitation, the analytical solutions of the mean output power, voltage and current are derived from Fokker–Planck (FP) equations. Monte Carlo simulation exhibits qualitative agreement with FP theory, showing that load values and excitation’s spectral density have an effect on the total m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Nevertheless, the effects of introducing nonlinear stiffness into a randomly excited hybrid PE and EM energy harvester on output characteristics could be quite different. Li et al [38] and Zhou et al [39] showed that a nonlinear hybrid energy harvester excited by white Gaussian noise could theoretically outperform its linear counterpart, which was validated by numerical and experimental methods, respectively. However, to the best of the authors' knowledge, there are no related studies for the response of a nonlinear hybrid piezoelectric-electromagnetic energy harvester when subjected to colored excitation, which represents a more realistic simulation of a practical vibration environment.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Nevertheless, the effects of introducing nonlinear stiffness into a randomly excited hybrid PE and EM energy harvester on output characteristics could be quite different. Li et al [38] and Zhou et al [39] showed that a nonlinear hybrid energy harvester excited by white Gaussian noise could theoretically outperform its linear counterpart, which was validated by numerical and experimental methods, respectively. However, to the best of the authors' knowledge, there are no related studies for the response of a nonlinear hybrid piezoelectric-electromagnetic energy harvester when subjected to colored excitation, which represents a more realistic simulation of a practical vibration environment.…”
Section: Introductionmentioning
confidence: 84%
“…In order to generate a nonlinear hybrid PE and EM energy harvester, two permanent magnets are used, located symmetrically on the mass magnet (see Figure 1). Introducing magnets as nonlinear component into hybrid piezoelectric and electromagnetic energy harvester will produce a linear factor 1 k and nonlinear factor 3 k based on references [38][39][40][41][42], hence it becomes a nonlinear hybrid piezoelectric and electromagnetic energy harvester, and its governing equation can be obtained as follows:…”
Section: Basic Structurementioning
confidence: 99%
See 3 more Smart Citations